2016
DOI: 10.1093/nar/gkw1133
|View full text |Cite
|
Sign up to set email alerts
|

The new NHGRI-EBI Catalog of published genome-wide association studies (GWAS Catalog)

Abstract: The NHGRI-EBI GWAS Catalog has provided data from published genome-wide association studies since 2008. In 2015, the database was redesigned and relocated to EMBL-EBI. The new infrastructure includes a new graphical user interface (www.ebi.ac.uk/gwas/), ontology supported search functionality and an improved curation interface. These developments have improved the data release frequency by increasing automation of curation and providing scaling improvements. The range of available Catalog data has also been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
1,912
1
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,012 publications
(1,942 citation statements)
references
References 21 publications
18
1,912
1
11
Order By: Relevance
“…Examining this further, we observed that this variant was highly pleiotropic with associations with several traits and diseases including Alzheimer's Disease, body mass index, C-reactive protein, highdensity lipoprotein cholesterol, low-density lipoprotein cholesterol, plasma triglycerides and waist circumference, hip circumference and waist-hip ratio at P = 6 x 10 -4 (Bonferroni corrected P = 0.05 / 82; see Supplementary Table 4). Furthermore, this variant was associated with several other traits and diseases in the public NHGRI-EBI GWAS catalog 21 (P < 5 x 10 -8 ; see Supplementary Table 5). After removing this outlier variant, we observed a lower estimation of the causal estimate of BMI on C-reactive .…”
Section: Pleiotropy Confounds Causal Estimates In Mr Testsmentioning
confidence: 99%
“…Examining this further, we observed that this variant was highly pleiotropic with associations with several traits and diseases including Alzheimer's Disease, body mass index, C-reactive protein, highdensity lipoprotein cholesterol, low-density lipoprotein cholesterol, plasma triglycerides and waist circumference, hip circumference and waist-hip ratio at P = 6 x 10 -4 (Bonferroni corrected P = 0.05 / 82; see Supplementary Table 4). Furthermore, this variant was associated with several other traits and diseases in the public NHGRI-EBI GWAS catalog 21 (P < 5 x 10 -8 ; see Supplementary Table 5). After removing this outlier variant, we observed a lower estimation of the causal estimate of BMI on C-reactive .…”
Section: Pleiotropy Confounds Causal Estimates In Mr Testsmentioning
confidence: 99%
“…To further identify genes associated with complex disease and to gather GWAS data, we used the November 28th, 2016 release of NHGRI-EBI's GWAS Catalog [10]. We filtered the catalog to remove nondisease traits, by keeping only entries that were children of the term "disease" (EFO 0000408) in the Experimental Factor Ontology [17].…”
Section: Methodsmentioning
confidence: 99%
“…We prefer this manually curated database to automatic text mining, because text mining may introduce false positives when a gene is mentioned in passing. We classified genes into those associated with Mendelian disease, complex disease, both, or no disease using the Online Mendelian Inheritance in Man (OMIM) database [9] and the EBI-NCBI GWAS catalog [10].…”
mentioning
confidence: 99%
“…The National Human Genome Research Institute -European Bioinformatics Institute Catalog of published GWAS Catalog lists ≈2500 such studies published since the first (in 2005), identifying ≈25 000 single-nucleotide polymorphism trait associations. 3 This approach has the benefit of being hypothesis-free, and unexpected associations between genetic variants and disease states discovered by GWAS have led to new biological insights.…”
Section: See Article By Rao Et Almentioning
confidence: 99%